Three essays on corporate finance - Kim, Hye Min (Nanyang Technological University, 2020)
Using a regression discontinuity design, I show that customer unionization causes suppliers to experience negative stock returns, rely less on these customers for their sales, and be more likely to terminate relationships with them. Suppliers reduce exposure to unionized customers due to the demand uncertainty arising from potential labor disruptions, reduction in customers’ competitiveness in the product market, and customers’ potential shifting of unionization costs to suppliers. However, customers’ unionization mitigates the effect of their default risks on their relationship with the suppliers, because, in this situation, their unions can advocate policies that also benefit the suppliers.